1996
DOI: 10.1002/j.1460-2075.1996.tb01081.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mammalian 20S proteasome biogenesis: the maturation of beta-subunits is an ordered two-step mechanism involving autocatalysis.

Abstract: Maturation of eukaryotic 20S proteasomes involves the processing of beta‐subunits by limited proteolysis. To study the processing mechanism we analysed different point mutations of the beta‐subunit LMP2 in transfected human T2 cells. Here we show that the presence of the intact Gly‐1Thr1 consensus motif and Lys33 are essential for correct processing. Mutation of Thr1, the active site residue in mature subunits, or of Lys33, results in complete inhibition of processing at the consensus site. In addition, propro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
166
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(177 citation statements)
references
References 61 publications
10
166
1
Order By: Relevance
“…In fact, proteasome inactivation has been shown to delay the autocatalytic processing step necessary for the final maturation step of the 20 S core complex (10,11,34,35). Therefore, the observed increase in the amount of proteasome subunits may in part be explained by the accumulation of proteasome precursor complexes (Fig.…”
Section: Up-regulation Of Proteasomal Mrnas Results In De Novo Formatmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, proteasome inactivation has been shown to delay the autocatalytic processing step necessary for the final maturation step of the 20 S core complex (10,11,34,35). Therefore, the observed increase in the amount of proteasome subunits may in part be explained by the accumulation of proteasome precursor complexes (Fig.…”
Section: Up-regulation Of Proteasomal Mrnas Results In De Novo Formatmentioning
confidence: 99%
“…These propeptides play an essential role during the biogenesis process and are processed by cis-or transautocatalysis in a two-step mechanism (10). The propeptides of the active ␤ subunits are cleaved off autocatalytically, whereas the propeptides of the inactive subunits are removed by their active neighbors (10 -13).…”
mentioning
confidence: 99%
“…The seven human alpha subunit cDNAs were amplified by RT-PCR and cloned in frame into the following vectors pET41 (Novagen), pCITE (Novagen), pGBT9 and pGAD GH (Clontech), generating constructs pET41-a 1-7 , pCITE-a 1-7 , pGBT9-a [1][2][3][4][5][6][7] and pGAD GH-a [1][2][3][4][5][6][7] . All constructs used in the study were sequenced to confirm identity and PCR fidelity.…”
Section: Preparation Of Expression Vectorsmentioning
confidence: 99%
“…We previously showed that assembly of mammalian 20S proteasomes is a multistep process that occurs via the formation of distinct proteasome precursor complexes with different ␤ subunit compositions. Active-site ␤ subunits are synthesized and incorporated as proproteins that essentially mature by a two-step procedure within the precursor complexes (12,13). Final activation of the ␤ subunits requires the formation of the preholoproteasome assembly intermediate.…”
mentioning
confidence: 99%